2022
DOI: 10.3390/ijms231911563
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of Phosphoserine Aminotransferase-Encoding Gene (AtPSAT1) Prompts Starch Accumulation in L. turionifera under Nitrogen Starvation

Abstract: It has been demonstrated that the phosphorylation pathway of L-serine (Ser) biosynthesis (PPSB) is very important in plant growth and development, but whether and how PPSB affects nitrogen metabolism and starch accumulation has not been fully elucidated. In this study, we took the energy plant duckweed (strain Lemna turionifera 5511) as the research object and used a stable genetic transformation system to heterologously over-expressing Arabidopsis AtPSAT1 (the gene encoding phosphoserine aminotransferase, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…This research suggests that the movement of the gate-keeping loop (residues 391–401) is a key element in regulating the catalytic activity of PSAT when 3-PHP binds to P-Ser. Overexpression of PSAT 1 in duckweed ( Lemna turionifera 5511) increases starch production by promoting light and nitrogen utilization [ 15 ]. Our investigation into PSAT ’s transcriptomic response to Cd stress revealed the downregulation of most genes in glycolysis and the TCA cycle, potentially resulting from biochemical reactions triggered by stress-induced injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research suggests that the movement of the gate-keeping loop (residues 391–401) is a key element in regulating the catalytic activity of PSAT when 3-PHP binds to P-Ser. Overexpression of PSAT 1 in duckweed ( Lemna turionifera 5511) increases starch production by promoting light and nitrogen utilization [ 15 ]. Our investigation into PSAT ’s transcriptomic response to Cd stress revealed the downregulation of most genes in glycolysis and the TCA cycle, potentially resulting from biochemical reactions triggered by stress-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Serine serves as a precursor for tryptophan, glycine, and cysteine, which are essential for nucleic acid and protein biosynthesis [ 14 ]. Furthermore, PSAT has been identified as a driver of starch accumulation in duckweed under nitrogen-starved conditions [ 15 ]. In our previous study, significant upregulation in the expression of both PSAT and GDH was observed during Cd stress [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, genes related to NAD (P)H, such as NADH-dependent glutamate synthase, NAD(P)H-quinone oxidoreductase subunit 4, NADH dehydrogenase (ubiquinone) Fe-S protein, NADH:quinone reductase, and NADHubiquinone oxidoreductase, showed significant up-regulation in resistant genotypes, confirming its role in energy homeostasis in plants under stress conditions. Other than NADH-related genes, shoot transcriptome data of resistant genotypes in the present study also showed significant up-regulation of other genes involved in energy metabolism, such as phosphoenolpyruvate carboxylase (Wang et al, 2016;Waseem and Ahmad, 2019), alcohol dehydrogenase (Su et al, 2020), alanine transaminase (Bashar et al, 2020), ATP citrate (pro-S)-lyase (Liu F. et al, 2022), ATPase , carbonic anhydrase (Rudenko et al, 2021), cytochrome c, cytochrome c oxidase (Guerra-Castellano et al, 2018;Analin et al, 2020), fructose-bisphosphate aldolase (Lv et al, 2017;Cai et al, 2022), malate dehydrogenase (Song et al, 2022), 6-phosphofructokinase 1 (Wang H. et al, 2021), photosystem II P680 reaction center D1 protein (Landi and Guidi, 2022), phosphoserine aminotransferase (Wang et al, 2022), pyruvate-orthophosphate dikinase (Yadav et al, 2020), and serine O-acetyltransferase (Mulet et al, 2004;Liu D. et al, 2022), and their molecular mechanism and role in energy homeostasis in different crops is well reviewed. It indicates that the significant up-regulation of the genes involved in energy metabolism in KWR 108 might have helped it to cope with Fusarium wilt stress by maintaining energy homeostasis in cells under stress conditions.…”
Section: Significant Up-regulation Of Energy Metabolism Genes In the ...mentioning
confidence: 97%